1978
DOI: 10.1111/j.1471-0528.1978.tb14931.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Serum Bilirubin Levels in Spontaneous and Induced Labour

Abstract: Summary An investigation was made into the onset and severity of neonatal jaundice in 114 patients following spontaneous labour and labour induced by (a) amniotomy, (b) amniotomy and simultaneous infusion of oxytocin, (c) amniotomy and simultaneous administration of oral prostaglandin E2, (PGE2,). No significant difference in serum bilirubin levels in the first five days of life was found in the four groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Others have speculated that oxytocin induction before the actual start of labor may be associated with a lack of hormonal surge present at spontaneous delivery, and hence a reduced activity of hepatic enzymes involved in bilirubin metabolism [4,5,6]. Our results, in accordance with others [10,11,21], failed to show any positive correlation between oxytocin induction and neonatal hyperbilirubinemia. Moreover, analysis of the results, · including phototherapy cases, indicated that oxytocin induction was associated with an attenuation of bilirubin levels both when vacuum extraction or spontaneous deliveries occurred.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Others have speculated that oxytocin induction before the actual start of labor may be associated with a lack of hormonal surge present at spontaneous delivery, and hence a reduced activity of hepatic enzymes involved in bilirubin metabolism [4,5,6]. Our results, in accordance with others [10,11,21], failed to show any positive correlation between oxytocin induction and neonatal hyperbilirubinemia. Moreover, analysis of the results, · including phototherapy cases, indicated that oxytocin induction was associated with an attenuation of bilirubin levels both when vacuum extraction or spontaneous deliveries occurred.…”
Section: Discussionsupporting
confidence: 58%
“…It is interesting to note that fetal scalp damage resulting in neonatal jaundice can be caused also by a fetal ,scalp electrode [7]. The association of oxytocin induction of labor and neonatal jaundice is still a matter of controversy [3,4,5,6,8,10,11,21]. It has been suggested that hyperbilirubinemia may result from an increased rate of red cell breakdown and hemoglobin catabolism secondary to increased intensity of uterine contractions [8] or decreased erythrocyte deformability [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of studies have associated oxytocin administration with neonatal hyperbilirubinaemia [15,16]. Oxytocin should be administered under constant observation by experienced personnel under continuous electronic monitoring of fetal heart and uterine activities.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand GOULD et al [11] in a prospective study, failed to demonstrate an effect of maternal oxytocin infusion on neonatal serum bilirubin levels on the first and sixth days of life. SIVASU-RIYA et al [20] similarly failed to find any difference in serum bilirubin levels in the first five days of life of neonates following spontaneous onset of labor and induced labor by various methods, including oxytocin infusion. A significant correlation between oxytocin administration and neonatal jaundice was claimed by DAVIES et al [7] äs being limited to artificially induced labors, and no difference was noted between spontaneous and oxytocin augmented, following spontaneous onset deliveries.…”
Section: Introductionmentioning
confidence: 98%